Exploring the Use of Collaborative Inquiry in Improving Practice - Panayiotis Angelides (Networks: An Online Journal for Teacher Research, 2003)
Effective teaching in mixed ability classes has dominated much of the Cyprus government's agenda for educational reform. Since the publication of the UNESCO report (UNESCO, 1997) which pointed out that primary school classes in Cyprus are organized as mixed ability groups with no clear policy about internal grouping, no policy on differentiation in curriculum, methodology or resource utilization, the Ministry of Education and Culture began a campaign for improving teaching in mixed ability classes. Circulars setting out the advantages of this policy were sent to schools and senior officials of the Ministry of Education and Culture organized seminars to suggest effective ways of teaching in mixed ability classes. In addition, in the 1990's primary school teachers in Cyprus passed through two major in-service training courses. One in the early 90's to enable them have equal financial rights with the secondary school teachers and another one five years later in order to get a bachelor's degree, since most of them had a diploma in education. Among other lessons they were also taught how to teach in mixed ability classes. However, there remains widespread dissatisfaction with Cyprus teachers' ability to teach in mixed ability classes. As the UNESCO (1997) report points out, classes are engaged in whole-class activity using a single textbook with the teacher teaching from the front of the class using an expository mode.